Islamic Law Reform In The Field Of Islamic Family Law In Indonesia - Azhari, Doni; Asmuni (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2024)
The purpose of this study is to investigate Islamic legal reform in Indonesian family law. A literature review and document analysis served as the foundation for the study. The research process began with a survey of the literature, which included a selection of books, academic papers, earlier studies, and pertinent government documents about the reform of Islamic family law. The purpose of this literature review was to comprehend the background, evolution, and application of family law reform in the context of Islamic law. A comparative study technique was used in the second part of the research to compare Indonesian Islamic family law with Islamic family laws in other nations that have enacted comparable reforms. The comparative study's findings revealed regional variations and convergences in approaches to the reform of Islamic family law. Without using the interview approach, the research attempts to provide a thorough knowledge of the evolution of Islamic family law reform in the environment under investigation by blending document analysis and literature evaluation.